The Secondary Surveillance Radar Parameters Extraction by Using of SIF/IFF Responses Analysis (Advances in Military Technology, 2022)
This article is focused on the possibility of extraction of Secondary Surveillance Radars parameters by using the responses SIF/IFF form planes. This extraction can be used for different goals as well as transponders location or interrogator testing. This article is focused especially on antenna rotation and pulse repetition interval extraction. For the posibility of these parameters extraction are used measured signal, i.e. received SIF/IFF codes and their time of arrival. The algorithms are tested by MATLAB.
Keywords: Secondary Surveillance Radar; Passive System; Parameters extraction